Analysis The Governance of Center Excellence Vocational School Program SMKS Yabhinka Cilegon on Improving Student Competence at the Industrial Era 4.0 - Dora Sembiring, Evi; Putri Pertiwi, Sari (PT Larva Wijaya Penerbit, 2025)
This research aims to analyze the governance of the Center of Excellence Vocational School program at Yabhinka Cilegon Vocational School in an effort to increase student competency to face the demands of the Industrial Era 4.0. The research method used is a qualitative approach with data collection techniques through interviews, observation and documentation studies. This research evaluates the planning, implementation and results of the program in improving student skills according to the needs of modern industry. The research results show that the governance of the Center of Excellence Vocational School program at Yabhinka Cilegon Vocational School has been running well through collaboration between the school, the business/industrial world (DUDI), and the government. This program has succeeded in integrating a technology-based curriculum and job market needs, increasing teacher capacity, and providing technology-based learning facilities. Overall, the Center of Excellence Vocational School program at Yabhinka Cilegon Vocational School has made a significant contribution in producing graduates who are competent, ready to face the demands of the Industrial Era 4.0, and able to compete in the global job market.